Sport Team Nonprofit Organizations: Are Sports Doing Well at "Doing Good"? - Emily Sparvero; Aubrey Kent (Journal of Applied Sports Management, 2014)
The outcomes and motivations of athletes and teams who engage in CSR activities are widely studied, but little to no attention has been paid to the management and operation of professional sport team nonprofit organizations (NPOs). In this study, the financial records of the charitable NPOs of 84 United States based professional sport teams from 2002 to 2010 were analyzed. Results indicate that there are differences in efficiency based on the ways in which team NPOs are classified. Additionally, team NPOs are compared to nonprofit industry standards, and the Team Nonprofit Score (TNS) is introduced as a tool to compare the financial efficiency and capacity of team NPOs to one another.
Keywords: sport teams; nonprofits; foundations; CSR